Disentangling patterns of economic, technological and innovative specialization of Western economies: An assessment of the Varieties-of-Capitalism theory on comparative institutional advantages - Meelen, A; Herrmann, A; Faber, J (Elsevier, 2017)
It is one of the central arguments of the Varieties-of-Capitalism (VoC) literature that national institutions determine comparative advantage. While Liberal Market Economies (LMEs) are said to offer comparative institutional advantages to firms that specialize in high-tech sectors based on radical innovation, Coordinated Market Economies (CMEs) offer advantages to firms specializing in medium-high-tech sectors characterized by incremental innovation. Several studies have tested these claims and arrived at contradictory results about specialization in line with institutional advantages. We argue that undifferentiated conceptualizations of the notion of specialization contribute to these inconclusive results. Based on the insights of the innovation literature on comparative advantage, we therefore disentangle the concepts of 1) economic specialization, 2) technological specialization, and 3) innovative specialization. Our analyses of panel data on exports and patents show that the VoC theory is rather weak in explaining patterns of economic specialization but can account for technological specialization. Furthermore, the VoC literature can hardly explain patterns of innovative specialization.